Numerical modelling on metallic materials - Wen, Shuwen; Sun, Yongle; Chen, Xin (MDPI, 2025)
Numerical modelling of metallic materials has emerged as a pivotal research area in modern materials science and engineering [...]
This article belongs to the Topic Numerical Modelling on Metallic Materials
Keywords: 40 Engineering; 4016 Materials Engineering; 4019 Resources Engineering and Extractive Metallurgy; 4016 Materials engineering; 4019 Resources engineering and extractive metallurgy